2016
DOI: 10.1186/s12884-016-1027-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the implementation of the postpartum haemorrhage management guidelines at the first regional perinatal centre in Southern Kazakhstan

Abstract: BackgroundPostpartum haemorrhage (PPH) remains one of the most common causes of maternal morbidity and mortality. Therefore, clearly written PPH management guidelines should be used in clinical practice. The aim of this study was to evaluate the effectiveness of the implementation of PPH management guidelines at the First Regional Perinatal Centre of Southern Kazakhstan (FRPC).MethodsBetween 2012 and 2013 an interventional study was performed whereby the PPH management guidelines were implemented at the FRPC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A similar study in Kazakhstan concluded that implementation of PPH management guidelines had a positive effect on PPH prevention, diagnostics, and management. The evidence suggested that guidelines led to a more deliberated approach to the treatment of PPH …”
Section: Discussionmentioning
confidence: 99%
“…A similar study in Kazakhstan concluded that implementation of PPH management guidelines had a positive effect on PPH prevention, diagnostics, and management. The evidence suggested that guidelines led to a more deliberated approach to the treatment of PPH …”
Section: Discussionmentioning
confidence: 99%
“…20 To date, there is a lack of information about the statistics of peripartum hysterectomy and its common indications in Central Asian countries. Some available data come from small regional cohorts, 21 however, it does not reflect the country-wide statistics. Taking into account this knowledge gap, we aimed to study the prevalence, indications, and outcomes of peripartum hysterectomy using nationwide large-scale health-care data from the national registry.…”
Section: Introductionmentioning
confidence: 99%